Epidemiology of Salmonella on the Paws and in the Faeces of Free-Ranging Raccoons (Procyon Lotor) in Southern Ontario, Canada - Bondo, K J; Pearl, D L; Janecko, N; Boerlin, P; Reid-Smith, R J; Parmley, J; Jardine, C M (Zoonoses and Public Health, 2016)
Raccoons are common in urban and rural environments and can carry a wide range of bacteria, including Salmonella, that can negatively affect human and livestock health. Although previous studies have reported that raccoons shed a variety of Salmonella serovars in their faeces, it is unknown whether Salmonella is carried on raccoon paws. Our objective was to compare the prevalence of Salmonella on the paws and in the faeces of raccoons in south-western Ontario. Raccoons were sampled in a repeat cross-sectional study on five swine farms and five conservation areas from May to October 2012. A total of 416 paired faecal and paw samples were collected from 285 individual raccoons. Salmonella was detected in 18% (75/416; 95% CI, 14-22%) and 27% (111/416; 95% CI, 22-31%) of paw and faecal samples, respectively. Salmonella was detected only on paws in 8% (35/416; 95% CI, 5.9-11.5%), only in faeces in 17% (71/416; 95% CI, 13.6-21.0%) and on both paws and in faeces in 10% (40/416; 95% CI, 7.0-12.9%) of raccoon captures. Multilevel logistic regression models were used to examine associations between the presence of Salmonella and age (adult, juvenile), sex (male, female), location type (swine farm, conservation area), sample type (faeces, paw) and season (May-July and August-October). Random intercepts were included to account for clustering by individual animal and location. Significant differences, that varied by sample type and season, were noted in the prevalence of Salmonella carriage between sexes. Raccoons can carry Salmonella serovars known to infect humans and livestock on their paws and/or in their faeces and therefore have the potential to mechanically and biologically disseminate Salmonella among livestock facilities and human recreational areas.
Keywords: ženské pohlaví; Female; Ontario; feces; Animals; salmonelová infekce u zvířat; Male; Feces; Raccoons; Salmonella Infections, Animal; zvířata; mývalové; noha (od hlezna dolů); Animals, Wild; Foot; mužské pohlaví; divoká zvířata; Salmonella